Rising Rates of Upfront Surgery in Early Locally Advanced Cervical Cancer: What Factors Predict for This Treatment Paradigm?. Issue 8 (1st October 2018) - Amini, Arya; Robin, Tyler P.; Stumpf, Priscilla K.; Rusthoven, Chad; Schefter, Tracey E.; Shinde, Ashwin; Chen, Yi-Jen; Glaser, Scott M.; Corr, Bradley R.; Fisher, Christine M.
Abstract : Objective: In this study, we analyzed patterns of care for patients with locally advanced cervical cancer to identify predictors for upfront surgery compared with definitive chemoradiation (CRT). Methods: The National Cancer Database was queried for patients aged 18 years or older with Federation of Gynecology and Obstetrics IB2–IIB cervical cancer. All patients underwent either upfront hysterectomy with or without postoperative radiation therapy versus definitive CRT. Logistic regression was used to assess variables associated with modality of treatment (surgery vs CRT). Results: Of the 9494 patients included, 2151 (22.7%) underwent upfront surgery. Of those undergoing surgery, 380 (17.7%) had positive margins, 478 (22.2%) had positive nodes, and 458 (21.3%) had pathologic involvement of the parametrium. Under multiple logistic regression, rates of surgery significantly increased from 2004 (12.2%) to 2012 (31.2%) (odds ratio [OR] per year increase, 1.15; confidence interval [CI], 1.12–1.17; P < 0.001). Upfront surgery was more commonly performed in urban (OR, 1.21; 95% CI, 1.03–1.41; P = 0.018) and rural counties (OR, 1.79; 95% CI, 1.24–2.58; P = 0.002), for adenocarcinoma (OR, 2.14; 1.88–2.44; P < 0.001) and adenosquamous (OR, 2.69; 2.11–3.43; P < 0.001) histologies, and in patients from higher median income communities (ORs, 1.19–1.37). Upfront surgery was less common at academic centers (OR, 0.73; 95% CI, 0.58–0.93; P = 0.011). Conclusions: Rates of upfront surgery relative to definitive CRT have increased significantly over the past decade. In the setting of level 1 evidence supporting the use of definitive CRT alone for these women, the rising rates of upfront surgery raises concern for both unnecessary surgical procedures with higher rates of treatment-related morbidity and greater health care costs.